Effect of flow resistance in open rectangular channel - Ahmad, Noor Aliza; Saiful Bahry, Saiful Iswal; Md Ali, Zarina; Mat Daud, Azra Munirah; Musa, Sabariah (EDP Sciences, 2017)
The determination of flow resistance for open channels remains a challenge in practices. In this research, an experimental study was carried out to investigate the hydraulic roughness characteristics in an open channel. The experimental flume (10 m length, 0.30 m width and 0.46 height) was carried out with two conditions ; contain gravel bed and without gravel bed (as controller). Blocks of concrete foam were fabricated and laid on the bed surface for providing uniformly roughened along the open channel. A velocity flow meter was used to quantify the average velocity, and other parameters such as cross-section, hydraulic radius, wetted perimeter, and channel slopes were also calculated. Finally, the flow resistance, n obtained using the flume with gravel bed surface is higher than the flume without gravel bed surface. The flow conditions were declared as subcritical as the Froude number is less than 1 for both conditions in the flume. As a conclusion, it was identified that the hydraulic roughness n, was influenced by the type bed roughness, flow rate and channel slope.